2016
DOI: 10.1264/jsme2.me15114
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Expression of <i>NodC</i> and Community Structure of Soybean-Nodulating Bradyrhizobia

Abstract: In order to assess the physiological responses of bradyrhizobia and competition for the nodulation of soybean at different temperatures, we investigated the expression of the nodC gene at 20, 25, and 30°C and the abilities of bacteria to nodulate soybean in microcosms at day/night cultivation temperatures of 23/18°C, 28/23°C, and 33/28°C for 16/8 h. We tested five Bradyrhizobium USDA strains: B. diazoefficiens USDA 110T and 122, B. japonicum USDA 123, and B. elkanii USDA 31 and 76T. The expression of nodC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Bradyrhizobium are versatile bacteria inhabiting soils and plants ( Zhalnina et al, 2013 ; VanInsberghe et al, 2015 ; Jones et al, 2016 ; Szoboszlay et al, 2017 ). Genomic and ecological studies have focused on soybean bradyrhizobia ( B. diazoefficiens and B. japonicum ) because of their prominent roles in nodule formation and their agricultural significance ( Masuda et al, 2016 ; Shiro et al, 2016 ; Saeki et al, 2017 ; Siqueira et al, 2017 ). However, photosynthetic diazotrophs often nodulate an aquatic legume, Aeschynomene , but sometimes lack nod genes ( Giraud et al, 2007 ; Okubo et al, 2012a ; Okazaki et al, 2016 ), and, thus, appear to function as an intermediate between free-living diazotrophs and classical nodulating diazotrophs ( Okubo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bradyrhizobium are versatile bacteria inhabiting soils and plants ( Zhalnina et al, 2013 ; VanInsberghe et al, 2015 ; Jones et al, 2016 ; Szoboszlay et al, 2017 ). Genomic and ecological studies have focused on soybean bradyrhizobia ( B. diazoefficiens and B. japonicum ) because of their prominent roles in nodule formation and their agricultural significance ( Masuda et al, 2016 ; Shiro et al, 2016 ; Saeki et al, 2017 ; Siqueira et al, 2017 ). However, photosynthetic diazotrophs often nodulate an aquatic legume, Aeschynomene , but sometimes lack nod genes ( Giraud et al, 2007 ; Okubo et al, 2012a ; Okazaki et al, 2016 ), and, thus, appear to function as an intermediate between free-living diazotrophs and classical nodulating diazotrophs ( Okubo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the known geographical distribution of bradyrhizobia strains in Japan and the United States ( 26 , 27 , 35 ). Furthermore, many studies have suggested that the relationship between genomic diversity and the field distribution of indigenous soybean-nodulating rhizobia is affected by soil environmental properties such as temperature being influenced by latitude and altitude, phosphorus content, EC, and soil pH ( 1 , 18 , 22 , 34 , 36 , 43 ). The present results also indicate that the mechanism of dominance in poorly aerated soils under field conditions is related to the denitrification activity of bradyrhizobia.…”
Section: Discussionmentioning
confidence: 99%
“…Root perception of NF leads to root hair deformation and rhizobial invasion of root cortical cells, via the infection thread, to elicit nodule formation. Suboptimal soil temperatures (less than 25°C) limit these stages of nodule establishment (Lindemann & Ham, 1979; Lynch & Smith, 1993; Matthews & Hayes, 1982), especially infection and early nodule development, because of limited nod gene expression and NF synthesis (Shiro, Kuranaga, Yamamoto, Sameshima‐Saito, & Saeki, 2016; Zhang & Smith, 1994). Cytokinin induces early nodulin genes in plants acting in a similar way to NF signalling, inducing cortical cell division genes (Bauer, Ratet, Crespi, Schultze, & Kondorosi, 1996; Dehio & de Bruijn, 1992; Heckmann et al, 2011; Mathesius, Charon, Rolfe, Kondorosi, & Crespi, 2000).…”
Section: Introductionmentioning
confidence: 99%